Study on workability and strength properties of concrete containing 0%, 5%, 15% and 25% quarry dust as fine aggregate replacement - Rohaizamri, Shuhaimin (2012)
Nowadays people are playing more attention to the sustainability in construction field. So, an engineers are finding the ways to improve the quality of the concrete using industrial waste such fly ash, quarry dust, polymer and silica. One of the methods is to mix the quarry dust with the concrete. In this research, a quarry dust waste was added in the different proportion by weight of cement. The effect of quarry dust as a sand replacement in concrete were investigated 36 numbers with dimension 150mm xlSOmm 150mm and beam specimen with dimension 150mm x 150mm x 750mm were prepared. Four different mix design containing 0% ,5%, 15% and 25% of quarry dust were designed as sample A, sample B, sample C and sample D respectively. Water cement ratio of 0.54 was constant. Cube samples were tested at age 7, 14 and 28 days while beam specimen were prepared at age 28 days. The slump test for sample A, sample B, sample C and sample D were 75 mm,35 mm,65 mm and 70 mm are respectively. All sample were fail in true slump. The compression strength of sample A,. sample B, sample C and sample D were 29.82N1mm 2 , 29.38N/mm2 , 29.43N/mm 2 and 30.18N/mm 2 are respectively. The flexural strength of sample A, sample B, sample C and sample D were 2.99 Mpa, 2.94Mpa,2.95Mpa and 3. 1OMpa respectively.